Design, Characterization and in vitro Simulations of nano-HAP/GO Composite Drug Delivery System Produced by Hydrothermal Methods Loaded with Paclitaxel - Çiftçi, Fatih (Sivas Cumhuriyet University, 2023)
In this study, it was aimed to develop a nano drug system that can be used in passive targeting in pancreatic cancer treatment. Hydroxyapatite nanocrystals (n-HAP) produced by hydrothermal process and graphene oxide (GO) produced by hummers method were used to increase the carrier capacity of the nano drug system and to activate the drug release kinetics and drug loading capacity. Analyses performed for nanocomposite drug carrier systems; FT-IR, XRD, TGA, BET analysis, Zeta potential, TEM and SEM. Paclitaxel (PTX), a chemotherapeutic drug used in the treatment of pancreatic cancer, was loaded into HAP nanocrystals (PTX- loaded n-HAP) and its activity on pancreatic cancer cells was investigated. When PTX was 1 and 2 mg, Encapsulation Efficiency (EE) and Drug Loading Content (LC) were 79.17-72.24% and 80.01-80.27%, respectively, for H-n-HAP crystal structure only, while EE and LC were 88.57-81.57% and 90.84-110.57%, respectively, when H-n-HAP crystal structure was loaded with 1 and 2 mg PTX together with GO. Here, it was observed PTX release profiles are according to the Hixson model. According to Fick's law, release profile was observed with values of k=1.89, n=0.21, SSD=0.04, R2=0.997, FIC=2.03, SD=0.004. In cell culture studies, as GO nanomaterials were loaded into H-n-HAP nanocrystal structure, the effect of PTX drug on pancreatic cancer increased and the viability of cancer cells decreased. It can be concluded that H-n-HAP/GO/PTX nanocomposite structure kills more pancreatic cancer cells with synergistic effect.
Keywords: Biodegradable Material; Graphene; Nano-structures; Nanocomposite; Biopolymer